Risiko penyakit jantung bawaan pada perkawinan konsanguinus - Aris Fazeriandy; Muhammad Ali (Fakultas Kedokteran USU, 2017)
Congenital heart disease (CHD) is the most common congenital anomaly and frequently found in children. The incidence of CHD worldwide is constant, approximately 8-10 of 1000 life births. The risk of CHD phenotype is higher if the parents have consanguineous marriage at a rate of 2-3 fold. In most cases, the cause of CHD is unknown. Among several risk factors, consanguineous marriage is one of the important factors. The role of consanguineous marriage in CHD is confirmed by previous studies reporting consanguineous marriage that showed autosomal recessive pattern in a few CHD cases. Keywords : Congenital heart disease, children, consanguineous marriage.